1978
DOI: 10.1002/pol.1978.180161004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pressure on the volume and the dielectric relaxation of linear polyethylene

Abstract: SynopsisThe effects of pressure on the a (ca. 7OoC, 1 kHz) and y (ca. -lOO°C, 1 kHz) relaxations of linear polyethylene were studied dielectrically between 0 and 4 kbar. Equation of state (PVT) data were also determined in the range of interest of these relaxations. The sample was rendered dielectrically active through oxidation (0.8 C=O per 1000 CH2). The a process (which occurs in the crystalline fraction) could he studied over a much wider temperature range than heretofore possible due to the effect of pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
2

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 15 publications
5
33
0
2
Order By: Relevance
“…In previous elevated pressure studorder parameters, typically Ç 0.025), and the ies on polymers, other researchers have found that samples were aged at atmospheric pressure for 48 similar silicone oils do not penetrate the exposed h after poling to allow the majority of the injected polymer at pressures up to 3000 atm. [22][23][24][25] Our DSC analysis confirmed these results in that no measur- not be removed from the substrate due to sample cracking; however, consistent data were still obtained. and Figure 4 it is clear that a negligible amount The temporal decay of the SHG signal from the of chromophore reorientation occurred during poled samples was measured using the optical cell heating at ú 3000 atm and the subsequent 10 s placed in the standard SHG configuration with pressure release period.…”
Section: Sample Preparationsupporting
confidence: 89%
“…In previous elevated pressure studorder parameters, typically Ç 0.025), and the ies on polymers, other researchers have found that samples were aged at atmospheric pressure for 48 similar silicone oils do not penetrate the exposed h after poling to allow the majority of the injected polymer at pressures up to 3000 atm. [22][23][24][25] Our DSC analysis confirmed these results in that no measur- not be removed from the substrate due to sample cracking; however, consistent data were still obtained. and Figure 4 it is clear that a negligible amount The temporal decay of the SHG signal from the of chromophore reorientation occurred during poled samples was measured using the optical cell heating at ú 3000 atm and the subsequent 10 s placed in the standard SHG configuration with pressure release period.…”
Section: Sample Preparationsupporting
confidence: 89%
“…First of all, our estimates are made at constant pressure, while the molecular mechanics (MM) minima of the listed works are to be compared with the constant volume experimental value. The experimental constant pressure activation energy of the a process in PE is 24.9 kcal/ mol, while the constant volume one is 19.4 AE 0.5 kcal/mol [13]. The earliest works [30,29] give the values 11.8 and 10.5 kcal/mol, for the conformational (of the type tg þ tg À tg þ t) twistecompression and the smooth (in a chain consisting of 22 CH 2 groups) twistetension defects, respectively.…”
Section: Energies Of Formation Of the Defects In Pe Crystalmentioning
confidence: 99%
“…The most striking draw ratio of 400 is obtained in dry gel films of PE [2], the simplest polymer which always served as a 'model system'. The presence of the chain diffusion through crystallites of PE is verified by direct 13 C NMR experiments in common melt-crystallized samples [3] and in samples of uncommon morphologies: fibers [3], electron beam irradiated samples [4] and even in single crystals [5].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…To a lesser extent dielectric techniques have been used to study the effect of pressure on the relaxations of phase materials [2][3][4][5][6][7][8][9]. By varying pressure, temperature and frequency, one can separate the activation energy and activation volume contributions to the activation enthalpy [4].…”
Section: Introductionmentioning
confidence: 99%